2020
DOI: 10.3389/fbioe.2020.564667
|View full text |Cite
|
Sign up to set email alerts
|

Chlorella vulgaris Extract as a Serum Replacement That Enhances Mammalian Cell Growth and Protein Expression

Abstract: The global cell culture market is experiencing significant growth due to the rapid advancement in antibody-based and cell-based therapies. Both rely on the capacity of different living factories, namely prokaryotic and eukaryotic cells, plants or animals for reliable and mass production. The ability to improve production yield is of important concern. Among many strategies pursued, optimizing the complex nutritional requirements for cell growth and protein production has been frequently performed via culture m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 39 publications
7
30
0
Order By: Relevance
“…Furthermore, when comparing CVE and DMEM, a trend of slightly higher viability with CVE than with DMEM was noted. Previous studies have shown that microalgal extracts may have antioxidant and serum‐substitution effects, which may have contributed to the slightly higher survival of PBMs in CVE culture than in DMEM cultures 26,27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, when comparing CVE and DMEM, a trend of slightly higher viability with CVE than with DMEM was noted. Previous studies have shown that microalgal extracts may have antioxidant and serum‐substitution effects, which may have contributed to the slightly higher survival of PBMs in CVE culture than in DMEM cultures 26,27 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that microalgal extracts may have antioxidant and serum-substitution effects, which may have contributed to the slightly higher survival of PBMs in CVE culture than in DMEM cultures. 26,27 Additionally, in this study, we analyzed PBM differentiation after cultivation using microalgal extracts. For the induction of PBM differentiation, low myotube formation capacity was observed with the use of ISS (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…We were intrigued by a recent study in which the authors reported growth effects of algae extract on mammalian cells (Ng et al, 2020). Ng and colleagues report that extract derived from Chlorella vulgaris promoted growth of Chinese hamster ovary (CHO) and mesenchymal stem cells (MSC) under certain conditions, some of which did not contain any serum.…”
Section: Introductionmentioning
confidence: 99%
“…Higher cell growth [49,50] Rice protein hydrolysate CHO-320 Human HepG cells Protection against oxidation stress from hydrogen peroxide [51,52] Soy peptones CHO DG44 Improved cell production [53] Wheat hydrolysates CHO Improved cell viability [54] Marine cyanobacterium Spirulina maxima Human Lung Carcinoma Improved cell viability and proliferation [55] Chlorella vulgaris extract CHO-K1 and MSC Promoted cell growth [56] Rapeseed caked CHO-C5 Promoted cell growth [57] Silk sericin hydrolysate CHO and Hela cells Improved cell growth and proliferation [58] Whey protein CHO K1 JURKAT E6. 1 Improved cell viability and proliferation [59] The matrices shown in Table 2 are those that achieved promising results in cell proliferation and viability.…”
Section: Higher Productivity Of Human Beta Interferonmentioning
confidence: 99%